A cost-effectiveness analysis of varenicline for smoking cessation using data from the EAGLES trial - Baker CL; Pietri G (Dove Medical Press, 2018)
Christine L Baker,1 Guilhem Pietri2 1Pfizer Inc., New York, NY, USA; 2Data Pyxis Ltd., St Albans, UK Background: The cost-effectiveness of varenicline has been demonstrated in the US health care setting using the Benefits of Smoking Cessation on Outcomes (BENESCO) model to simulate the lifetime direct costs and consequences of a hypothetical cohort of US adult smokers who make a single attempt to quit. The aim of this study was to undertake an updated cost-effectiveness analysis, using current epidemiology inputs and recently published smoking cessation data from the Evaluating Adverse Events in a Global Smoking Cessation Study (EAGLES), the largest clinical trial of smoking cessation pharmacotherapies conducted to date.Methods: BENESCO is a Markov model simulating the effect of a single attempt to quit smoking on four smoking-related diseases: coronary heart disease, stroke, chronic obstructive lung disease, and lung cancer. Inputs were updated to include efficacy from EAGLES and newer data for the epidemiology of smoking in the US, the epidemiology and direct treatment costs of the four morbidities, and the costs of the interventions. Analyses compared varenicline, bupropion, nicotine replacement therapy (NRT) patch, and placebo with regard to the incidence of smoking-related morbidity, the incidence of smoking-related mortality, and cost-effectiveness at a time horizon from 2 years to lifetime.Results: The study cohort comprised of 18,394,068 US adult smokers who made a single quit attempt during the first year of the model. For varenicline, there were an estimated 319,730 fewer smoking-related morbidities at the lifetime compared with placebo. Similarly, smoking-related mortality decreased by 198,240 subjects when varenicline was compared with placebo. For the same time horizon, varenicline was more effective and less costly, ie, dominant, compared with all comparators in the cost-effectiveness analysis.Conclusion: Based on the BENESCO model, smoking cessation with varenicline results in reduced incidence of smoking-related morbidity and mortality compared with other smoking cessation interventions and remains a cost-effective strategy in the US population. Keywords: cost-effectiveness, smoking cessation, varenicline, BENESCO model, EAGLES trial, smoking-related morbidity, smoking-related mortality